Modified Natural Rubber Sir-20 Using Chain Scission Reaction Method And Grafting With Anhydrous Maleic - April Sinaga; Eddyanto Eddyanto; Andreas Nababan (Universitas Negeri Medan, 2022)
In this research, natural rubber SIR-20 was modified by the chain severing reaction method with the addition of decimal peroxide and flowing oxygen gas as much as 2 l/mint for 6 hours at a temperature of 135oC while stirring. Fourier Transformed-Infra Red (FTIR) spectra obtained, it can be concluded that there has been a chain breaking reaction seen from the functional group analysis which produces a series of distinctive peaks in the hydroxyl group (OH) and 2 carbonyl peaks (C=O) which are obtained at natural rubber SIR-20 + 3 phr DCP of 3435 and 1715, respectively; 1737 and has a strong intensity which indicates a chain breaking reaction has occurred in natural rubber SIR-20. From the results of the FTIR analysis, it was found that the C=O group was getting sharper which was the typical absorption peak originating from maleic anhydride grafted on the natural rubber chain.